The Effect of Simvastatin on Thyroid Function in Experimental Autoimmune Thyroiditis Induced in Rats - Mohammed, Yaqeen Talib; Hameed Mohameed , Nadia; Samih Arif, Inaam (Iraqi Journal of Pharmaceutical Sciences, 2024)
Autoimmune thyroiditis or Hashimoto’s thyroiditis (HT): is the most common autoimmune thyroid disease. is characterized by marked lymphocytic infiltration and the presence of serum autoantibodies against Thyroid peroxidase (TPO) and Thyroglobulin (TG). HT is a prevalent cause of hypothyroidism in areas of the world where dietary iodine is sufficient. Genetic predisposition and cellular and humoral immunity play a role in thyroid autoimmune pathogenesis. Antithyroid antibodies are produced by interaction between APC, T cells, and B cells to fix complement. Thyroid tissue is more severely damaged by complement-dependent antibody-mediated cytotoxicity. Statins, the powerful inhibitors of HMG-CoA reductase have pleotropic effects including anti-inflammatory and immunomodulatory effects. In this current study, Experimental autoimmune thyroiditis was induced in twenty-four female Wistar rat. Simvastatin was given at a dose of 4mg/kg for 30 days. Thyroid autoantibodies and Thyroid hormones were measured by ELISA technique Results showed that Simvastatin reduced autoantibodies against TPO and TG. It also lowered serum level of TSH and increased serum level of T4. Due to the undesirable side effects associated with the current treatment options used in Autoimmune thyroiditis. Simvastatin might be a promising approach in the treatment of this disease.